Engineers' guide to pressure equipment : the pocket reference / Clifford Matthews. - Matthews, Clifford (Mechanical Engineering, 2001)
This is an introduction to the technical and administrative aspects of vessel manufacture and use, covering the basic principles of pressure equipment design, manufacture, quality assurance and inspection, and operation.